2005
DOI: 10.1093/nar/gki605
|View full text |Cite
|
Sign up to set email alerts
|

Internal initiation of translation of the TrkB mRNA is mediated by multiple regions within the 5' leader

Abstract: Translational regulation of the dendritically localized mRNA encoding for the neurotrophin receptor TrkB has important ramifications for synaptic function. We examined whether the TrkB mRNA is translated through an internal initiation entry site (IRES). The human TrkB 5′ leaders are derived from the use of alternative promoters and alternative splicing, but all 5′ leaders share a common exon. Insertion of a full-length 5′ leader, as well as the common exon into the intercistronic region of a dicistronic lucife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…The former by definition applies only to mRNAs bearing CPEs, whereas the latter controls eIF4-PABP-mediated translation, including cap-dependent translation and IRES-mediated translation using EMCV-like mechanisms. Several dendritic mRNAs have been reported to harbor IRES elements, indicating that they may be locally translated in a 5Ј end-independent manner (Pinkstaff et al, 2001;Dobson et al, 2005). Internal ribosome entry would provide a means for independent regulation of translation initiation in dendrites, differentiating it from the mostly capdependent mode in somatic translation.…”
Section: Translational Control In Germ Cells and Neuronsmentioning
confidence: 99%
“…The former by definition applies only to mRNAs bearing CPEs, whereas the latter controls eIF4-PABP-mediated translation, including cap-dependent translation and IRES-mediated translation using EMCV-like mechanisms. Several dendritic mRNAs have been reported to harbor IRES elements, indicating that they may be locally translated in a 5Ј end-independent manner (Pinkstaff et al, 2001;Dobson et al, 2005). Internal ribosome entry would provide a means for independent regulation of translation initiation in dendrites, differentiating it from the mostly capdependent mode in somatic translation.…”
Section: Translational Control In Germ Cells and Neuronsmentioning
confidence: 99%
“…during conditions of cellular stress or stages of the cell cycle). Alternative splicing coupled with the regulation of IRES activity has been reported for the mRNA encoding the neurotrophin receptor TrkB (50). However, although both the elk-1 mRNA 5′ UTR L and 5′ UTR S gave weak but positive read-outs in the bicistronic assay, this was readily attributable to cryptic promoter activity from the transfected DNA plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…2002). It has been shown that these five exons form an internal ribosome entry site (IRES) guiding the ribosome to the translational start site which is located in exon 5 (Dobson et al. 2005).…”
mentioning
confidence: 99%